2014
DOI: 10.4238/2014.november.12.3
|View full text |Cite
|
Sign up to set email alerts
|

Physical wounding and ethylene stimulated embryogenic stem cell proliferation and plantlet regeneration in protocorm-like bodies of Phalaenopsis orchids

Abstract: ABSTRACT. Phalaenopsis orchids have been regenerated by inducing protocorm-like bodies (PLBs) from etiolated leaf sections. However, the physiological and molecular mechanisms of secondary PLB development and subsequent proliferation have not been explored. Bisectionally cutting primary PLBs resulted in more secondary PLBs at 5 weeks, suggesting an embryogenic stem cell property imposed by wounding of primary PLB tissues. The ethylene precursors ethephon and 1-aminocyclopropanecarboxylic acid and the ethylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…The seeds were then sterilized with 0.6% sodium hypochlorite solution for 10 min then washed 3 times with sterile water. Later the sterilized seeds were sown on a germination medium containing Hyponex (7N-6P 2 O 5 -19K 2 O) plus 1 g l −1 Bacto-tryptone, 50 g l −1 potato homogenate, 50 g l −1 banana homogenate, 30 g l −1 sucrose, 2 g l −1 activated charcoal, and 7.5 g l −1 agar as reported previously (Huang et al 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…The seeds were then sterilized with 0.6% sodium hypochlorite solution for 10 min then washed 3 times with sterile water. Later the sterilized seeds were sown on a germination medium containing Hyponex (7N-6P 2 O 5 -19K 2 O) plus 1 g l −1 Bacto-tryptone, 50 g l −1 potato homogenate, 50 g l −1 banana homogenate, 30 g l −1 sucrose, 2 g l −1 activated charcoal, and 7.5 g l −1 agar as reported previously (Huang et al 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…2) after removal of the primary PLB apical parts to prevent apical dominance. Huang, Tsai, Cheng, Chen, & Chen (2014) have reported the formation of many secondary PLB structures in the epidermal layer around the excised PLBs. The addition of TDZ to the PLB proliferation medium did not show any significant effect on all parameters during the PLB proliferation (Table 3).…”
Section: Effects Of Tdz and Pvp On Plb Proliferationmentioning
confidence: 99%
“…In addition, Ng and Saleh (2011) suggested that PGR-free medium could obtain genetically stable PLBs. In recent years, secondary PLB development from PLBs has been shown for various orchids, including Dendrobium (Julkiflee et al, 2014), Doritaenopsis (Amaki and Higuchi, 1989), and Phalaenopsis (Huang et al, 2014;Khoddamzadeh et al, 2011). However, the results in this study showed that both large and small PLBs formed secondary PLBs (PLB proliferation) at nearly the same rates over 2, 4, and 6 weeks of culture (Fig.…”
Section: Resultsmentioning
confidence: 50%
“…This may be because the whole PLB and the upper side of the PLB still had many cell clumps around apical meristems that it would protrude and develop after 2 weeks. Others have shown that the lower halves of bisected PLBs are more efficient in the proliferation of secondary PLBs (Amaki and Higuchi, 1989;Huang et al, 2014;Tanaka, 1987).…”
Section: Resultsmentioning
confidence: 99%